High-Density Genetic Mapping Identifies New Major Loci for Tolerance to Low-Phosphorus Stress in Soybean - Zhang, Dan; Li, Hongyan; Wang, Jinshe; Zhang, Hengyou; Hu, Zhenbin; Chu, Shanshan; Lv, Haiyan; Yu, Deyue (Frontiers in Plant Science, 2016)
Phosphorus (P) is essential for all living cells and organisms, and low-P stress represents a major constraint on plant growth and yield worldwide. Soybean is an important economical resource of protein and oil for human and animals, and soybean is also a high-P demand species that is sensitive to low-P stress, which is considered a major constraint on soybean production. However, P efficiency is an important complex quantitative trait involving multiple genes, and the mechanisms underlying soybean P efficiency are largely unknown. Here, we reported the construction of a high-density genetic map using a specific-locus amplified fragment sequencing (SLAF-seq) strategy in soybean. This map, spanning 3020.59 cM in length, contained 6,159 markers on 20 chromosomes, with an average distance of 0.49 cM between adjacent markers. Based on this map, 20 loci, including eight novel loci, associated with P efficiency-related traits were identified across multiple years and treatments. The confidence intervals of almost all QTLs were refined significantly, and the accuracy of this map was evidenced by coincident detections of the previously identified P efficiency-related genes GmACP1 and GmPT1. Notably, a highly significant novel QTL located on chromosome 4, q4-2, was identified across traits, years and treatments. Several candidate genes, such as a pectin methylesterase-encoding gene (Glyma.04G214000) and a protein kinase gene (Glyma.13G161900), with significantly differential expression upon low-P stress were considered as promising candidates involved in regulating soybean P efficiency. Markers that tightly associated with P efficiency could be used for marker-assisted selection in a soybean P efficient breeding program. Further dissection of these QTLs will facilitate gene cloning underlying P efficiency in soybean, and increase our understanding of efficient use of P in enhancing crop yield.